La gamificación como metodología activa en el proceso de enseñanza-aprendizaje: Caso de estudio: estudiantes de la carrera de Pedagogía de las Artes - Jaramillo Mediavilla, Lorena (Revista Ecos de la Academia, 2022)
This research addresses the study of gamification as a teaching - learning strategy in the training of students of the Pedagogy of Arts and Humanities career at the Universidad Técnica del Norte, this study is based on the need to incorporate new technologies to achieve educational purposes through active methodologies that are used to enhance student engagement and interaction. It is a qualitative - descriptive research in an action research framework since it intends to incorporate gamification as a learning strategy within the teaching process and in the training of the students of the career. The results obtained show that gamification aims to introduce structures from games to convert a static activity into another activity that motivates people to participate in them. In conclusion, it was found that gamification is an educational innovation strategy used by many innovative teachers to change behaviors through incentives, social and individual reinforcements or prizes, among other components that make them highly attractive and can be applied in learning processes. teaching-learning.
Keywords: gamification, game, active methodologies, reinforcement, recreational activities, educational technology.